Exploration of lignocellulolytic microbes in oil palm rhizosphere on peat soils and their respiration activities - Siswanto; Saeful Anwar; Supiandi Sabiham; Husni Mubarok; Darmono Taniwiryono; Basuki Sumawinata; Heru B. Pulunggono; Happy Widiastuti (Microbiology Indonesia, 2021)
Microbial respiration in peatlands plays a role in contributing CO2 emissions. Studies of microbial exploration and respiration on peat soils in oil palm plantations have not been widely reported. This study aims to explore lignocellulolytic microbes found in peat soils in compared with mineral soils planted with 12-year-old oil palm. Exploration is done by growing the samples on the specific medium of each group of microbial functions. In the next stage, the culture obtained was analysed the respiration activity based on the oxidation of peroxidase catalysis using a chromogen substrate (tetramethylbenzidine) and measured using spectrophotometry at a wavelength of 450 nm. The results showed that both in mineral and peat planted with oil palm in a depths of 0-20 cm were found lignolytic fungi with a population of 17 x 102. Similar results were also found in peat with fern vegetation but at a depth of 20-40 cm. Lignolytic bacteria (methylene blue degradation) can be found on peat soils planted with oil palm at a depth of 0-60 cm and the population increases with increasing depth. This bacterium is also found on peat soils with fern vegetation and mineral soils planted with palm. At a depth of 0-20 cm the population of lignolytic bacteria in non-oil palm peat is highest. Cellulolytic bacteria were isolated at a depth of 0-60 cm. Cellulolytic bacterial populations were highest in oil palm peat at all depths compared to other samples. Respiration analysis of several dominant isolates showed fairly high variation between microbial function groups and within the same function group. The lignolytic microbial group degrading methylene blue showed high respiration activity and varies greatly (0.19-1.85 MER). While the respiration activity of cellulolytic bacteria ranged from 0.45 to 0.62 MER.